2015
DOI: 10.1186/s12889-015-1615-7
|View full text |Cite
|
Sign up to set email alerts
|

The total sale of prescription drugs with an abuse potential predicts the number of excessive users: a national prescription database study

Abstract: BackgroundPrescription drug sales may vary considerably across regions and over time. This study aimed to assess whether there is an association between mean drug sales and prevalence of excessive use in a range of psychotropic prescription drugs with an abuse potential, and if so, whether the variation in mean drug sales mostly reflects variation in the prevalence of excessive use or mostly reflects variation in non-excessive use.MethodsData on all filled prescriptions taken from the Norwegian prescription da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
(24 reference statements)
1
15
0
2
Order By: Relevance
“…The empirical support of the TCM with regard to gambling resembles that from the alcohol epidemiology literature (Norströ m et al, 2002;Rossow & Norström, 2013;Skog, 1985) and fits into a more general picture of the distribution of health hazards and incidence of health problems in populations (Bramness & Rossow, 2010;Rose, 2001;Rose & Day, 1990;Rossow & Bramness, 2015). In line with Rose (2001;Rose & Day, 1990) and Skog (1985), such regularities in population distributions suggest that factors at the population or aggregate level also impact on the level of excessive consumption and related harm.…”
Section: Discussionsupporting
confidence: 55%
“…The empirical support of the TCM with regard to gambling resembles that from the alcohol epidemiology literature (Norströ m et al, 2002;Rossow & Norström, 2013;Skog, 1985) and fits into a more general picture of the distribution of health hazards and incidence of health problems in populations (Bramness & Rossow, 2010;Rose, 2001;Rose & Day, 1990;Rossow & Bramness, 2015). In line with Rose (2001;Rose & Day, 1990) and Skog (1985), such regularities in population distributions suggest that factors at the population or aggregate level also impact on the level of excessive consumption and related harm.…”
Section: Discussionsupporting
confidence: 55%
“…Because the incident use of pregabalin is four times higher than that observed with gabapentin, the likelihood that vulnerable subjects will be exposed to misuse or to other adverse outcomes is higher for pregabalin . This situation has been observed previously in similar contexts with other drugs …”
Section: Discussionmentioning
confidence: 52%
“…In the USA, the increased pregabalin use has also been related to 'off-label' use as an alternative to opioids for various pain management [108]. Moreover, Rossow and Bramness [109] have shown that the consumption of prescription drugs with an abuse potential is skewedly distributed and that few excessive users account for a disproportionately high proportion of the drug sales.…”
Section: Recommendations To Authoritiesmentioning
confidence: 99%